ITERATIVE FORMULAS FOR SOLVING LINEAR DIFFERENTIAL EQUATIONS OF I AND II ORDER - Kujumdžieva-Nikoloska, Marija (Matematichki Bilten, 1993)
In this paper some iterative methods (1.2)((1.3)), (2.2)((2.3)), (3.3)((3.4)) for solving homogeneous linear differential equations (1), (2), (3) of I and II order with analytical coefficients are presented.